Bio-inspired vortex lift for enhanced manoeuvrability - Dominguez, Alejandro; Tomé, Joao; Gowree, Erwin Ricky; Bauerheim, Michaël (2022)
Inspired by highly manoeuvrable species of birds like the peregrine falcon and the swift, static and dynamic computational fluid dynamics (CFD) simulations were conducted to investigate vortex lift in unsteady flows. The configuration corresponds to a 50◦ sweep delta wing with sharp leading edge at Re= 5.0×104. CFD simulations were performed using a Direct Numerical Simulation (DNS) approach with a Lattice-Boltzmann Method as well as Unsteady Reynolds Averaged Navier-Stokes (URANS) simulations. Aerodynamic forces as well as the overall structure of the leading edge vortices were compared with existing literature. The evolution of the flow structures was studied when the wing performs a pitching manoeuvre from 0◦ to 20◦ angle of attack. Close agreement between both methods was found for the static and pitching lift curves, with the URANS solver presenting substantial limitations to capture complex unsteady phenomena such as the vortex breakdown. A time lag was observed in the flow dynamics during the manoeuvre, with the vortex breakdown delayed during pitch-up resulting in an improved aerodynamics performance, but more present and intense when pitching down. A sinusoidal motion was tested with the URANS solver and compared with the linear ramp case, showing performance advantages as well as higher similarity to real manoeuvres.